An Analysis on Students’ Creative Thinking Ability in Writing Narrative Paragraph - Hasfira, Hasfira; Ayu, Citra; Hardi, Vitri Angraini (Journal of Education Research, 2024)
This research was conducted at the second semester of English Education at the University of Pahlawan Tuanku Tambusai Bangkinang in academic year two thousand twenty-two to two thousand twenty-three. The purpose of this research is to describe the student’s creative thinking ability on writing narrative paragraph. The sample in this research is thirty-two students. The instrument of this research is test. The research is descriptive qualitative research. The researcher used several data analysis techniques are data reduction, display data, conclusion/verification. Based on data analysis, the results are analyzed from five categories: very high, high, medium, low, very low. The result of this research was seven students in the very high category, three of students in the high category, four of students in the medium category, two of students in the low category, of students in the very low category. Therefore, it can be concluded that the students creative thinking ability in writing narrative paragraph at the second semester of English Language and Education at the University of Pahlawan Tuanku Tambusai is very low.